The Macroeconomics of Corporate Debt. Issue 3 (14th August 2020) - Brunnermeier, Markus; Krishnamurthy, Arvind
Abstract: The 2020 COVID-19 crisis can spur research on firms' corporate finance decisions and their macroeconomic implications, similar to the wave of important research on banking and household finance triggered by the 2008 financial crisis. What are the relevant corporate finance mechanisms in this crisis? Modeling dynamics and timing considerations are likely important, as is integrating corporate financing considerations into modern quantifiable macroeconomics models. Recent empirical work, including articles in this special issue, on the drag from debt in the COVID-19 crisis provides a first glimpse into the new research agenda. ( JEL E22, E44, G32, G33) Received July 23, 2020; editorial decision: July 23, 2020 by Editor Andrew Ellul